Deficiency and the access to information: a reflection through communication and information paradigms - Oliveira, Eliza (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2019)
New paradigms and new realities emerge in the human society in current days, characterizing a society that questions its segregation culture, glimpsing new paths towards social inclusion of people with cerebral palsy. This scenario encourages scientific research, contributing to the evolution of available technological resources for accessibility. The significance of Communication and Information Technologies can be observed in a context in which, not just information shows a prominent role, but the ways to access it. The main goal of this article is to discuss, in the light of Technological and Complexity Paradigms, about the access to information by people with cerebral palsy, through Information and Communication Technologies. These technological resources are considered as Assistive Technology, once they promote accessibility for people with cerebral palsy by using user interfaces, which are especially relevant for the proposal reflection in this document.